Pendampingan Masalah Cybernullying Pada Kegiatan Literasi Digital untuk Siswa SMPN 1 Siman Ponorogo - Niken Rosyiana Puspitasari; Muhammad Adib Busoleh; Nadiva Dwi Suyatno; Novita Ria Anjani; Qomariyah Qomariyah; Yoga Fahay Romdhoni; Nurul Malika (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to identify assistance with cyberbullying problems using digital literacy for students at SMP N 1 Siman in the importance of implementing digital literacy in schools, steps for assisting students with cyberbullying problems, and strengthening in assisting cyberbullying problems among students. This research method uses a qualitative approach, with data collection techniques using observation, interviews and research literature. The data analysis technique uses the Miles and Huberman model, namely simplifying data according to needs, this makes it easier to obtain information, present data in the form of descriptions, and draw conclusions. The results of the research show that assistance with cyberbullying problems in digital literacy activities for students at SMP N 1 Siman has been implemented well.